Case Report of a Long-surviving Man with Metastatic Renal Cell Carcinoma Treated with Pazopanib. Issue 2 (March 2014) - Ratta, Raffaele; Santini, Daniele
Renal cell carcinoma is the most common type of kidney cancer in adults. It accounts for approximately 3% of adult malignancies and 90–95% of neoplasms arising from the kidney. At the moment several biological agents are used for the treatment of metastatic renal cell carcinoma. We describe the case of a man who has been treated with pazopanib (Votrient) for metastatic renal cell carcinoma since July 2011. At the time of writing, the patient is still receiving treatment (29 months) and is showing a long-lasting response with a favorable safety profile. This is an excellent example of chronic neoplastic disease in a patient who can be defined as long-surviving.